Analisis Minat Penggunaan Platform Merdeka Mengajar Dengan Sikap Guru SMP XYZ Bekasi Sebagai Variabel Intervening - Setyaningrum, Prima; Susanto, Hendro (Research and Community Service UNIVERSITAS KALBIS, 2024)
Platform Merdeka Mengajar (PMM) was created to help teachers understand the kurikulum merdeka, implement the kurikulum merdeka and develop teacher competency. The research aims to analyze interest in using PMM. This research uses the Technology Acceptance Model and Theory of Planned Behavior approach. The research population was XYZ Bekasi Middle School teachers who used PMM. Data analysis using SmartPLS 3.2.9. The research results show that the perceived usefulness and perceived convenience of PMM will have a positive and significant effect on attitudes towards using PMM; perceived usefulness of PMM has a direct positive and significant effect on interest in using PMM; Perceived usefulness of PMM will not influence attitudes towards using PMM through the attitude variable; the perceived ease of PMM has a direct effect on interest in using PMM; The perceived ease of PMM will have a positive and significant effect on attitudes towards using PMM through the attitude variable; and namely the attitude of PMM users will have a positive and significant effect on interest in using PMM.